Animal aided therapeutic lansdcape for drug rehabilitaion centers - Montero, Mariae Roneen Crystal Savier S.; Nadal, Cathe Desiree S. (Quezon City College of Architecture, University of the Philippines Diliman, 2014)
“By ourselves we can enjoy life, but to really appreciate life we must find companionship” - Anonymous
It is natural for people to crave for companionship and people usually find the need for having companions in other people and in our pets. Pets are known for providing their owners other benefits that is totally different from the said animals. Such benefits include: relieving stress, providing companionship and security. There is existing studies that incorporate a medically-approved class of therapy animals, which are usually dogs that are brought to carry-out animal-assisted therapy, this therapy is known as Animal Aided Therapy. (2010)
“Animal Aided Therapeutic Landscape for Drug Rehabilitation Centers” focuses on introducing and exploring a new kid of opportunity to make use of the concept in Rehabilitation Centers. The study focuses on providing a landscape area that would be able to aid in the facilitation and would cater to the need of the target users which are the choses animal that would be incorporated in the landscape and the patients of the Rehabilitation Center.
Incorporation of different areas that cater to the needs of both of the potential users and integration of these areas in one landscape showed that successful integration of these two concepts is indeed possible. The framework resulting from the study could become a template and a guide for other researchers that would choose to dwell and explore the possibilities of providing a landscape for Animal Aided Therapies.
Thesis (Bachelor of Landscape Architecture)--University of the Philippines Diliman
Keywords: Animals Therapeutic use; Animal welfare